Hierarchical molecular design of high-performance infrared nonlinear Ag2HgI4 material by defect engineering strategy. (July 2021) - Yang, C.; Liu, X.; Teng, C.; Cheng, X.; Liang, F.; Wu, Q.
Abstract: Mid-far infrared nonlinear optical (NLO) materials are gaining both scientific and technological interest in wide applications. The practical properties of one crystal are determined by its constituent atoms, electrons, lattices and their coupled interaction. Herein, by applying a hierarchical molecular design strategy, we synthesized a promising NLO material Ag2 HgI4 by a simple solution method, which shows the strongest second harmonic generation (SHG) response in inorganic halides (4 × AgGaS2 (AGS)) and wide transparency range. The deep insights on nonlinearity enhancement and broadening transmittance were elaborated by theoretical calculations, which are attributed to reduced phonon frequency and increased nonbonding electronic states on top valence band. This physical mechanism is applicable in all NLO optical materials generally, opening a novel and exciting avenue for explorations of new NLO candidates with high performance. Graphical abstract: Ag2 HgI4 is demonstrated to be a promising infrared NLO crystalline material, which has large SHG, high LDT, and wide infrared transparency range, concurrently. Image 1 Highlights: A defect diamond structure Ag2 HgI4 was synthesized by a hierarchical molecular design strategy. It exhibits large SHG intensity, high LDT, and wide infrared transparency range. Ag2 HgI4  is demonstrated to be a promising infrared NLO crystalline material